POTENTIAL WOUND HEALING MATERIALS FROM THE NATURAL POLYMERS -A review - VIJI CHANDRAN S,; TRIKKURMADOM SEETHARAMAN AMRITHA,; RAJALEKSHMI G,; PANDIMADEVI M, (International Journal of Pharma and Bio Sciences, 2015)
Wound healing represents a major health burden and the variety of wound types has resulted in a wide range of wound dressings with new products frequently introduced to target different aspects of the wound healing process. These wound dressing biomaterials play an active role in the healing process, thus accelerating the process. An ideal dressing should achieve rapid healing at reasonable cost with minimal inconvenience to the patient. The selection of an appropriate dressing plays an important role in both recovery and aesthetic appearance of the regenerated tissue. Among the various wound dressing materials, biomaterial or natural polymer based dressing are gaining importance because of their unique properties. This paper provides a review of the various biomaterials, bioactive polymers, polysaccharides, nano biocomposites, enzymes, growth factors that can be used as potential wound dressing material.